The Effect of Career Development and Job Satisfaction on Employee Performance at PT. Pupuk Sriwidjaja Division Operational Unit P-1B Palembang - Handanal Handanal; Badia Perizade; Zunaidah Zunaidah (International Journal of Social Service and Research, 2023)
This research aims to analyze the influence of career development and job satisfaction on employee performance at PT. Pupuk Sriwidjaja Palembang. The data collection technique in the research used a questionnaire with 121 employees at PT. Pupuk Sriwidjaja Palembang as respondents. Data analysis uses multiple linear regression with model testing. The research results show that career development has a positive and significant effect on employee performance at PT. Pupuk Sriwidjaja Palembang. Job satisfaction has a positive and significant effect on employee performance at PT. Pupuk Sriwidjaja Palembang.